Optimization of Cryopreservation Technique for Human Cord Blood Nucleated Cells Using Combination of Cryoprotectant DMSO and Antioxidant N-acetyl-L-cysteine - Makashova, Olena E.; Babijchuk, Lyubov O.; Zubova, Oksana L.; Zubov, Pavlo M. (Problems of Cryobiology and Cryomedicine, 2016)
The paper evaluated the efficiency of N-acetyl-L-cysteine (AC) antioxidant for cryopreservation of human cord blood nucleated cells (CBNCs) with various concentrations of endocellular cryoprotectant dimethyl sulfoxide (DMSO). It has been found that rise in DMSO concentration (from 2.5 and 5 up to 7.5% and 10%) and exposure time of the CBNCs suspension with cryoprotectant (from 15 to 30 min and longer) resulted in a significant increase in the amount of cells with excess reactive oxygen species (ROS) (from (7.5 ± 0.8)% at 5% DMSO and 15-min incubation to (28.9 ± 3.2)% with 10% DMSO and 60 min incubation), decrease in their viability and preservation rate. Supplementing 10 mM AC to the cryopreservation medium led to a reduction in the amount of cells with excess ROS and rise of their preservation rate and viability at the stage of equilibration with cryoprotectant, as well as after freeze-thawing of CBNCs suspension. Maximum effect was achieved after AC supplementing to the media with 7.5 and 10% DMSO concentrations. We proved that the use of antioxidant contributed to the rise in preservation rate and viability of CBNCs if cryoprotectant concentration and exposure time with it were optimal. Probl Cryobiol Cryomed 2016; 26(4): 295–307.